Assessment of the Structure of an Old Ex-Hotel Building for Change Function into a Shopping Center as Building Permit Approval - Nurokhman, Nurokhman; Masduqi, Edy; Kusumaningrum, Evy (CV. Strata Persada Academia, 2025)
This study evaluates the structural condition of the former Hotel Mutiara I building in Yogyakarta, which is undergoing a change of function into a shopping center. In compliance with Indonesian regulations, such as Law No. 28 of 2002 and SNI standards, the structural assessment focuses on safety and feasibility under increased live loads. Using a combination of destructive and non-destructive testing methods, including Core Drill Tests, Pulse Velocity Tests, and Ultrasonic Concrete Tomography, the study analyzes the quality of concrete and reinforcement materials. The findings reveal that the building's concrete compressive strength exceeds the minimum requirement of 21 MPa, indicating acceptable material performance for its age. However, deficiencies, such as plain reinforcement bars and inadequate concrete cover, necessitate compliance upgrades. The increased live load of 6.00 kN/m² due to the change in function requires structural reinforcement, particularly for columns and beams. Recommended measures include applying Carbon Fiber Reinforced Polymer (CFRP) to enhance axial, shear, and bending capacities and addressing non-compliant structural elements. This research underscores the importance of comprehensive structural evaluations for aging buildings undergoing functional changes, offering practical recommendations to ensure long-term safety, compliance, and functionality while preserving historical architectural integrity.